Building a Low Carbon Indian Economy. Issue 1 (June 2021) - Kathpal, S; Kumar, K; Kumar, P; Mishra, S
Abstract: Climate change has bought unprecedented challenges to humanity. The world has witnessed the dark side of climate change in terms of rising sea level and increase in temperature of world. Low carbon emission is the key to minimize the impact of climate change. Widespread significance attached to reduction in carbon emission has given birth to the new notion of low carbon economy (LCE). The LCE suggests sustainable development of economy by minimizing the ecological damage through the adoption of green practices. The countries across the globe are aiming to become LCE. This paper provides insights into the new notion of low carbon economy and how India is moving towards the encouraging path to become low carbon economy to tackle impending climate change and balancing its developmental needs.